Genus Diplectrona Westwood 1840 (Insecta: Trichoptera) in India - Pandher, Manpreet Singh; Kaur, Simarjit; Garima, Deepti; Parey, Sajad H. (Zootaxa, 2021)
This paper is another contribution to knowledge of the caddisfly fauna of India. We redescribe and illustrate Diplectrona marginata Betten 1909 based on previously collected material as well as from fresh collections. The status of D. marginata is validated after Betten (1909) and Martynov (1935) and a neotype is designated for D. marginata because the remaining syntype has been damaged and is not identifiable. Furthermore, D. kinulta Oláh et al. 2020 is considered a synonym of D. marginata based on the similarity of male genitalia. Diplectrona aurovittata (Ulmer 1906) is reported for the first time from India, bringing the number of Indian species of Diplectrona to 10.